Long-term effects of alum-treated litter, untreated litter and NH4NO3 application on phosphorus speciation, distribution and reactivity in soils using K-edge XANES and chemical fractionation. (1st May 2018) - Abdala, D.B.; Moore, P.A.; Rodrigues, M.; Herrera, W.F.; Pavinato, P.S.
Abstract: Whereas soil test information on the fertility and chemistry of soils has been important to elaborate safe and sound agricultural practices, micro-scale information can give a whole extra dimension to understand the chemical processes occurring in soils. The objective of this study was to evaluate the effects that the consecutive application of untreated poultry litter, alum-treated litter or ammonium nitrate (NH4 NO3 ) had on P solubility in soils over 20 years. For this, we used soil test data, sequential chemical fractionation (SCF) of P, and P K-edge XANES and μ-fluorescence spectroscopies. Water extractable P data indicated that application of alum to poultry litter was a very effective treatment for reducing P solubility. On the basis of our SCF of P data, P was primarily found within the 0.1 M NaOH pool across the applied rates and regardless of the treatment, where application of alum-treated litter accounted for as much as 59 ± 2% of the total, followed by NH4 NO3, 49 ± 4%, and untreated litter, 40 ± 2%. It was also shown that in soils where alum-treated litter was applied, the Resin pool accounted for 10 ± 1% of the total, followed by NH4 NO3, 13 ± 4%, and untreated litter, 18 ± 2%, indicating that P was less readily available in soils where alum-treated litter was applied. Phosphorus XANES indicated that P was predominantly associated to Fe > Al > Ca > organic molecules, regardless of the treatment or applied rates, though the formation of PoAl complexes was only found in soils that received application of alum-treated litter and was positively related to the applied rates. The combination of P-XANES with SCF or μ-fluorescence data was shown to provide valuable information about P reactivity and distribution in soils and should thus be used to address the fate of applied P amendments in soils. Highlights: Long-term application of alum-treated litter to soils leads to the formation of PoAl complexes. Application of alum to poultry litter is an effective treatment to reduce P solubility. Overall, sequential chemical P fractionation is well correlated to P-XANES results. P-XANES showed that P was predominantly associated to Fe > Al > Ca > organic molecules, irrespectively of the treatment or applied rates. P partitioning between Al and Fe-minerals was strongly dependent on the type of applied litter, i.e., treated or not with alum.